Genome Sequence of an M3 Strain of Streptococcus pyogenes Reveals a Large-Scale Genomic Rearrangement in Invasive Strains and New Insights into Phage Evolution - Nakagawa, Ichiro; Kurokawa, Ken; Yamashita, Atsushi; Nakata, Masanobu; Tomiyasu, Yusuke; Okahashi, Nobuo; Kawabata, Shigetada; Yamazaki, Kiyoshi; Shiba, Tadayoshi; Yasunaga, Teruo; Hayashi, Hideo; Hattori, Masahira; et al. (Genome Research, 2003)
Group Astreptococcus (GAS) is a gram-positive bacterial pathogen that causes various suppurative infections and nonsuppurative sequelae. Since the late 1980s, streptococcal toxic-shock like syndrome (STSS) and severe invasive GAS infections have been reported globally. Here we sequenced the genome of serotype M3 strain SSI-1, isolated from an STSS patient in Japan, and compared it with those of other GAS strains. The SSI-1 genome is composed of 1,884,275 bp, and 1.7 Mb of the sequence is highly conserved relative to strain SF370 (serotype M1) and MGAS8232 (serotype M18), and almost completely conserved relative to strain MGAS315 (serotype M3). However, a large genomic rearrangement has been shown to occur across the replication axis between the homologous rrn-comX1 regions and between two prophage-coding regions across the replication axis. Atotal of 1 Mb of chromosomal DNA is inverted across the replication axis. Interestingly, the recombinations between the prophage regions are within the phage genes, and the genes encoding superantigens and mitogenic factors are interchanged between two prophages. This genomic rearrangement occurs in 65% of clinical isolates (64/94) collected after 1990, whereas it is found in only 25% of clinical isolates (7/28) collected before 1985. These observations indicate that streptococcal phages represent important plasticity regions in the GAS chromosome where recombination between homologous phage genes can occur and result not only in new phage derivatives, but also in large chromosomal rearrangements.